2018
DOI: 10.1007/s00441-018-2875-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of functional cardiomyocytes from human umbilical cord-derived virus-free induced pluripotent stem cells

Abstract: We have previously demonstrated that human umbilical cord-derived mesenchymal stem cells (UC-MSCs) can differentiate into cardiomyocyte-like cells. However, no contracting cells were observed during differentiation. In this study, we generated induced pluripotent stem cells (iPSCs) from UC-MSCs using mRNA reprogramming and focused on the differentiation of reprogrammed iPSCs into functional cardiomyocytes. For cardiac differentiation, the spontaneously contracting cell clusters were present on day 8 of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…1 d; Supplement F. 1a-e). The above results indicated that human UMSCs could be successfully reprogrammed into iPSCs with well-defined cellular and molecular characteristic using the mRNA-based method which was in agreement with the previous study [ 8 , 9 , 32 ]. Overall, the above results strongly indicated that the iPSCs generated with the mRNA cocktails were human pluripotent stem cells with truly rejuvenation and pluripotent state and total two background iPSCs lines were established and used for further experiments in our study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…1 d; Supplement F. 1a-e). The above results indicated that human UMSCs could be successfully reprogrammed into iPSCs with well-defined cellular and molecular characteristic using the mRNA-based method which was in agreement with the previous study [ 8 , 9 , 32 ]. Overall, the above results strongly indicated that the iPSCs generated with the mRNA cocktails were human pluripotent stem cells with truly rejuvenation and pluripotent state and total two background iPSCs lines were established and used for further experiments in our study.…”
Section: Resultssupporting
confidence: 92%
“…Also, another study has presented an optimized procedure to produce MSCs from human iPSCs depends on the generation of embryoid bodies (EBs) and transforming growth factor beta 1 (TGF-β1) [ 7 ]. In addition, Wu et al, has showed anti-BMP2 Ab/BMP2 immune complex was capable of promoting osteogenic differentiation of iPSCs going through iMSCs, which may be a favorable approach for iPSC-based bone tissue engineering [ 8 , 9 ]. Above studies have shown that iMSCs can be successfully differentiated from iPSCs with well-defined differentiation procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that when body tissues suffer from ischemia-anoxia injury or chronic inflammation, the damaged tissue released chemokines, mobilized and guided the migration of MSCs to the injury site, and further induced differentiation into different types of cells ( Kidd et al, 2010 ). In vitro culture, UC-MSCs can be “trans-differentiated” under certain conditions to become mesoderm cells such as osteoblasts ( Xue et al, 2018 ) and cardiomyocytes ( Wu et al, 2018 ), endothelial cells ( Motawea et al, 2020 ), and also can differentiate into neurons in the ectoderm, hepatocytes ( Zhou et al, 2017 ), pancreatic cells ( Van Pham et al, 2014 ) in endoderm between germ layer. The low immunogenicity, high proliferation and differentiation potential of UC-MSCs make them seed cells for cell replacement therapy.…”
Section: Biological Characteristics Of Uc-mscsmentioning
confidence: 99%
“…More importantly, compared to other sources of adult stem cells, there is a lower risk of viral contamination due to the protection provided by the placental barrier (Duya et al, 2013). In addition, studies have shown that hUCMSCs can differentiate into chondrocytes, osteoblasts, cardiomyocytes, and neurons, and hUCMSCs have been applied for cartilage regeneration, and bone tissue regeneration, and to treat kidney injury (Wang et al, 2016;Day et al, 2018;Wu et al, 2018;Zhang et al, 2018;Zheng et al, 2019). However, whether hUCMSCs can be applied in dental pulp regeneration remains unknown.…”
Section: Introductionmentioning
confidence: 99%